Proses Asuhan Gizi Terstandar pada Pasien Pediatri Bronkopneumonia dan Kejang Demam Sederhana Pasca Konvulsi dengan Pemberian Diet Tinggi Kalori dan Tinggi Protein: Sebuah Laporan Kasus - Fera Feheliani Cristanti; Trias Mahmudiono; Erfiana (Universitas Airlangga, 2024)
Background: Pediatric patients diagnosed with bronchopneumonia and post-convulsive simple febrile seizures need special nutritional care to prevent damage to body tissues, restore the body and fulfill nutritional intake. In addition, patients with bronchopneumonia and post-convulsive simple febrile seizures sometimes experience decreased appetite and inadequate food consumption. Nutritional Care Process (NCP) by providing a high-calorie and high-protein diet is carried out in order to provide food as needed, thus helping to speed up the healing process and minimizing the occurrence of disease complications. Objectives: To determine the management of standardized nutritional care processes in pediatric patient’s bronchopneumonia and post-convulsive simple febrile seizures by providing a high-calorie and high-protein diet. Methods: The case study was conducted in January 2023 on inpatients at RSI Jemursari Surabaya. The research sample was obtained by selecting patients based on specific criteria, including patients who were hospitalized for more than 3 days and experienced complications related to the disease. Sampling was conducted by reviewing the patient's medical history in medical records, with the approval of the attending nurse and in the presence of a hospital nutritionist. The method applied to patients involves interviewing the patient's parents to assess the physical domain, monitoring the patient's medical record to evaluate the biochemical domain, and observing the patient's food intake for 3 consecutive days. This is done by recording 9 meals through 24-hour food recall and visual comstock. Researchers also conducted literature reviews to gather the necessary information. Results: After monitoring and evaluation carried out for 3 days, it was found that the patient's body temperature was in the normal range (no fever), the patient's weight was constant/fixed, biochemical indicators could not be observed for increases or decreases because there were no laboratory results the following day, and Fulfillment of the patient's nutritional intake for 3 consecutive days shows a gradual increase in results up to> 80%. Conclusions: In this case, the patient’s recovery was quite rapid. There was an increase in appetite and food consumption gradually increased to >80%. Overall, the nutritional intervention was achieved.